1994
DOI: 10.1002/jor.1100120213
|View full text |Cite
|
Sign up to set email alerts
|

Nonuniform distribution of collagen density in human knee ligaments

Abstract: It is generally recognized that the mechanical properties of soft connective tissues are affected by their structural components. We documented collagen density distributions in human knee ligaments to quantify differences in density within and between these ligaments. In order to explain the variations in mechanical properties within and between different knee ligaments as described in the literature, the distributions of collagen density were correlated with these biomechanical findings. Human knee ligaments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 14 publications
2
17
0
Order By: Relevance
“…Mommersteeg et al 58 found that orientation of loading at the knee is more critical in the cruciate ligaments compared with the collaterals and that loading orientation may affect the tensile stiffness of the ACL. Mommersteeg and colleagues59 also showed that collagen density is different between human ACL and MCL, with the ACL showing significantly lower collagen density compared with the MCL. Variations in collagen density have been shown to correspond to differences in Young’s modulus for the ACL and MCL 60.…”
Section: Valgus Collapse Mechanism: a More Recent Discovery And Probamentioning
confidence: 98%
“…Mommersteeg et al 58 found that orientation of loading at the knee is more critical in the cruciate ligaments compared with the collaterals and that loading orientation may affect the tensile stiffness of the ACL. Mommersteeg and colleagues59 also showed that collagen density is different between human ACL and MCL, with the ACL showing significantly lower collagen density compared with the MCL. Variations in collagen density have been shown to correspond to differences in Young’s modulus for the ACL and MCL 60.…”
Section: Valgus Collapse Mechanism: a More Recent Discovery And Probamentioning
confidence: 98%
“…Facet capsular and other ligaments have varied fiber organization and density in different subregions where nerves have been identified and across different anatomic ligaments [1,[86][87][88][89]. The specific anatomy of a ligament can lead to varied macroscopic and microscopic mechanical responses especially for varied loading directions and under different loading rates.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the biochemical composition of ligaments has been studied in an effort to explain the observed material property inhomogeneities. 153,154 Frank et al 153 studied the normal rabbit MCL and found different levels of water content, glycosaminoglycan content and collagen concentration along the length of the ligament. Mommersteeg et al 154 showed that collagen density is nonuniformly distributed throughout human knee ligaments.…”
Section: Materials Properties Of Ligamentsmentioning
confidence: 99%